Návrh, tvorba a implementace softwarové aplikace ve firemním prostředí - Pohořelský, Michal (Vysoké učení technické v Brně. Fakulta podnikatelská, 2023)
Diplomová práce je zaměřena na problematiku plánování a vývoje softwaru. Cílem práce je naplánovat vývoj desktopové aplikace jako rozšíření informačního systému ERP Prytanis. Aplikace se nazývá Odbyt a doplňuje funkcionalitu modulu informačního systému zajišťující evidenci skladového hospodářství. Aplikace slouží pro správu požadavkových listů jinak řečeno objednávek došlých.

The master thesis focuses on the issues of software planning and development. The aim of the thesis is to plan the development of a desktop application as an extension of the ERP Prytanis information system. The application is called Sales and it complements the functionality of the information system module providing the inventory management. The application is used to manage request lists, in other words, incoming orders.
Design, Creation and Implementation of Software Applications in the Corporate Environment
Keywords: vývoj desktopové aplikace; .Net WinForms; DevExpress; projektový management; vodopádový model; development of desktop application; .Net WinForms; DevExpress; project management; waterfall model